Increased microbial activity in a warmer and wetter climate enhances the risk of coastal hypoxia. Issue 2 (18th April 2013) - Nydahl, Anna; Panigrahi, Satya; Wikner, Johan
Abstract: The coastal zone is the most productive area of the marine environment and the area that is most exposed to environmental drivers associated with human pressures in a watershed. In dark bottle incubation experiments, we investigated the short‐term interactive effects of changes in salinity, temperature and riverine dissolved organic matter (rDOM) on microbial respiration, growth and abundance in an estuarine community. An interaction effect was found for bacterial growth, where the assimilation of rDOM increased at higher salinities. A 3 °C rise in the temperature had a positive effect on microbial respiration. A higher concentration of DOM consistently enhanced respiration and bacterial abundance, while an increase in temperature reduced bacterial abundance. The latter result was most likely caused by a positive interaction effect of temperature, salinity and rDOM on the abundance of bacterivorous flagellates. Elevated temperature and precipitation, causing increased discharges of rDOM and an associated lowered salinity, will therefore primarily promote bacterial respiration, growth and bacterivore abundance. Our results suggest a positive net outcome for microbial activity under the projected climate change, driven by different, partially interacting environmental factors. Thus, hypoxia in coastal zones may increase due to enhanced respiration caused by higher temperatures and rDOM discharge acting synergistically.